Classification of Transcranial Doppler Signals Using Artificial Neural Network - Serhatlio?lu, Selami; Hardalaç, Firat; Güler, Inan (My University, 2003)
Transcranial Doppler signals, recorded from the temporal region of brain on 110 patients were transferred to a personal computer by using a 16-bit sound card. The fast Fourier transform (FFT) method was applied to the recorded signal from each patient. Since FFT method inherently can not offer a good spectral resolution at jet blood flows, it sometimes causes wrong interpretation of transcranial Doppler signals. To do a correct and rapid diagnosis, transcranial Doppler blood flow signals were statistically arranged so that they were classified in artificial neural network. Back propagation neural network and self-organization map algorithms of artificial neural network were used for training, whereas momentum and delta-bar-delta algorithms were used for learning. The results of these algorithms were compared in the case of classification and learning.
Keywords: Artificial neural network; Backpropagation neural network; FFT; Self-organization map; Transcranial Doppler